EVALUASI PROGRAM PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR - Neliyanti '; Meyzi Heriyanto (Jurnal Kebijakan Publik, 2013)
This study aimsto evaluate the implementation of the activities of The Program Pemberdayaan Ekonomi MasyarakatPesisir (PEMP) on Micro Finance Institutions in Dumai. This type of research is descriptiveresearch with qualitative approach. Informants in this study are the actors who play a role inPEMP program, in accordance with the Organization’s Program Manager PEMP in Dumai. Resultsof the study concluded that the implementation of the management of the DEP by USP inCooperative Kerapu is seen from the indicators of effectiveness, efficiency, sufficiency, equity,responsiveness and precision, there is still a lot of shortcomings. None of the evaluation indicatorsthat are used can be fulfilled in the implementation of the management of the DEP.